Suppression of Annual Bluegrass Seedheads with Mefluidide, Ethephon, and Ethephon plus Trinexapac‐Ethyl on Creeping Bentgrass Greens. (1st November 2013) - Haguewood, John B.; Song, Enzhan; Smeda, Reid J.; Moss, Justin Q.; Xiong, Xi
Abstract : Annual bluegrass ( Poa annua L.) is a problematic weed on creeping bentgrass ( Agrostis stolonifera L.) putting greens. Annual bluegrass produces extensive seedheads in spring, and plant growth regulators (PGRs) are frequently used to suppress seedhead formation. This study investigated the effects of single and sequential applications of mefluidide, maleic hydrazide, and ethephon alone or in combination with trinexapac‐ethyl (TE), on annual bluegrass seedhead formation. A secondary objective evaluated whether addition of TE enhanced the efficacy of ethephon while improving the safety on creeping bentgrass. Three independent studies were established on golf course greens during a 2‐yr period, with initial PGRs application before annual bluegrass seedhead formation. Regardless of PGR treatment, single or sequential applications in all studies showed no differences in annual bluegrass seedhead suppression. Ethephon‐containing treatments provided the best seedhead suppression with up to 95% reduction. No PGR treatments caused visible phytotoxicity to creeping bentgrass following single applications. Sequential applications of both mefluidide and maleic hydrazide caused significant phytotoxicity to creeping bentgrass for up to 3 wk after initial treatment (WAIT). With the exception of one evaluation date in the third study, tank mixture of TE with ethephon had little effect on annual bluegrass seedhead suppression. Tank‐mixing TE with ethephon marginally enhanced turf quality of creeping bentgrass up to 6% compared to ethephon alone.